Advantages of Tissue Level Implants in Case of Alveolar Ridge and Mucosal Atrophy - Kublashvili, Marika; Dolidze, Tamar (European Scientific Journal, ESJ, 2023)
In the modern market, there is a great variety of dental implants, which differ from each other in design, geometry, connection type, surface treatment technology, etc. However, the most fundamental and main differentiating component between implants is how the implants are inserted into the bone and how it is positioned in relation to the soft tissues. Accordingly, they are divided into sunken, i.e., bone-level implants, and non-sunken, i.e., tissue-level implants, in which case the implant-abutment connection, or interface, is located at the gum level. This study shows the advantages of tissue-level implants in the case of atrophy of the alveolar ridge and also studies the comparison of bone lost in the case of bone-level implants and tissue-level implants.